Answer:
x = 3 and 7
There are two true solutions.
Explanation:
To solve
, use inverse operations by squaring both sides of the equal sign.
![(x-7)^2 = (√(-4x+28))^2\\x^2-14x+49 = -4x+28\\x^2-14x+4x+49-28 = 0\\x^2-10x+21=0](https://img.qammunity.org/2019/formulas/mathematics/college/emmdxb728jquhy4abg0jv8k4ke5tm8yhku.png)
The quadratic expression can be factored into binomials and set equal to 0 by the zero product property to find x.
(x - 3) ( x - 7) = 0
x-3 = 0 so x=3
x-7 = 0 so x=7
Now check each solution into the original equation to be sure it solve the solution and is not extraneous.
![7-7 = √(-4(7)+28)\\ 0=0](https://img.qammunity.org/2019/formulas/mathematics/college/bfrx6wuqwodoqkra7x3nijonqct5rsy0ty.png)
and
[/tex]